Clinical and Prognostic Value of Antigen-Presenting Cells with PD-L1/PD-L2 Expression in Ovarian Cancer Patients - Pawłowska, Anna; Kwiatkowska, Agnieszka; Suszczyk, Dorota; Chudzik, Agata; Tarkowski, Rafał; Barczyński, Bartłomiej; Kotarski, Jan; Wertel, Iwona (International journal of molecular sciences, 2021)
The latest literature demonstrates the predominant role of the programmed cell death axis (PD-1/PD-L1/PD-L2) in ovarian cancer (OC) pathogenesis. However, data concerning this issue is ambiguous. Our research aimed to evaluate the clinical importance of PD-L1/PD-L2 expression in OC environments. We evaluated the role of PD-L1/PD-L2 in OC patients (n = 53). The analysis was performed via flow cytometry on myeloid (mDCs) and plasmacytoid dendritic cells (pDCs) and monocytes/macrophages (MO/MA) in peripheral blood, peritoneal fluid (PF), and tumor tissue (TT). The data were correlated with clinicopathological characteristics and prognosis of OC patients. The concentration of soluble PD-L1 (sPD-L1) and PD-1 in the plasma and PF were determined by ELISA. We established an accumulation of PD-L1+/PD-L2+ mDCs, pDCs, and MA in the tumor microenvironment. We showed an elevated level of sPD-L1 in the PF of OC patients in comparison to plasma and healthy subjects. sPD-L1 levels in PF showed a positive relationship with Ca125 concentration. Moreover, we established an association between higher sPD-L1 levels in PF and shorter survival of OC patients. An accumulation of PD-L1+/PD-L2+ mDCs, pDCs, and MA in the TT and high sPD-L1 levels in PF could represent the hallmark of immune regulation in OC patients.